The Relevance of Tabula Rasa Theory in Digital Learning: A Systematic Literature Review - Arnoldus Helmon; Herman Dwi Surjono; Jumadi Jumadi; Rahayu Fuji Astuti; Agung Wahyu Hermansyah; Wong Yoke Seng (Lembaga Bale Literasi, 2025)
The development of digital learning has encouraged a re-examination of various theoretical foundations in education, including the relevance of tabula rasa theory, which views knowledge as developing through learning experiences. This study aims to synthesize research findings on tabula rasa theory in the context of digital learning and to examine its implications for instructional design and the development of educational technology. The method employed is a Systematic Literature Review (SLR) conducted through stages of identification, screening, eligibility assessment, and systematic synthesis of the literature to identify research trends, major themes, and forms of conceptual implementation in technology-based educational practices. The results of the review indicate that tabula rasa theory remains relevant, particularly in emphasizing the importance of learning experiences, interaction with the learning environment, and instructional designs that are adaptive to learners’ needs. Flexible, interactive, and data-driven digital learning further reinforces the importance of learner-centered instructional design that prioritizes meaningful learning experiences. The findings suggest that tabula rasa theory continues to hold conceptual value in understanding experience-based learning processes; however, it needs to be integrated with contemporary learning theories to remain relevant to the complexity of digital learning and the ongoing development of educational technology.